Booms and Slumps in World Commodity Prices - McDermott, C. (IMF Working Papers; Working Paper, 1999)
This paper examines the duration and magnitude of commodity-price cycles. It finds that for most commodities, price slumps last longer than price booms. How far prices fall in a slump is found to be slightly larger than how far they rebound in a subsequent boom. There is little evidence of a consistent 'shape' to commodity-price cycles. For all commodities, the probability of an end to a slump in prices is independent of the time already spent in the slump, and for most commodities, the probability of an end to a boom in prices is independent of the time already spent in the boom.